Imaging the Visual Network in the Migraine Spectrum - Puledda, Francesca; Ffytche, Dominic; O'Daly, Owen; Goadsby, Peter J. (Frontiers in Neurology, 2019)
The involvement of the visual network in migraine pathophysiology has been well known for more than a century. Not only is the aura phenomenon linked to cortical alterations primarily localized in the visual cortex; but also migraine without aura has shown distinct dysfunction of visual processing in several studies in the past. Further, the study of photophobia, a hallmark migraine symptom, has allowed unravelling of distinct connections that link retinal pathways to the trigeminovascular system. Finally, visual snow, a recently recognised neurological disorder characterized by a continuous visual disturbance, is highly comorbid with migraine and possibly shares with it some common pathophysiological mechanisms. Here we review the most relevant neuroimaging literature to date, considering studies that have either attempted to investigate the visual network or have indirectly shown visual processing dysfunctions in migraine. We do this by taking into account the broader spectrum of migrainous biology, thus analysing migraine both with and without aura, focusing on light sensitivity as the most relevant visual symptom in migraine, and finally analysing the visual snow syndrome. We also present possible hypotheses on the underlying pathophysiology of visual snow, for which very little is currently known.